CLL/S Detuned compensation network for electric vehicles wireless charging application - Aziz, Ahmad Fuad Abdul; Romlie, Mohd Fakhizan; Zulkifli, Tun Zainal Azni (Institute of Advanced Engineering and Science, 2019)
An electric vehicle (EV) can be charged wirelessly through an inductively coupled power transfer system where the system resonates the inductive coupling coil at the operating frequency by means of a compensation network. However, the resonant behaviour implies overcurrent in the inverter MOSFETs during uncoupled and high load resistor conditions, which affect to the inverter MOSFETs failure whenever the current exceeds their maximum current rating. Therefore, this paper presents a CLL/S detuned compensation network for EV wireless charging application to limit the inverter current during the uncoupled state and open circuit load conditions. The proposed compensation consists of a series capacitor and parallel inductor at the primary side and series capacitor at the secondary side. By using Kirchhoff Voltage Law (KVL) analysis, the primary side is detuned to inductive behaviour to ensure zero voltage switching (ZVS), and the secondary side remains at natural resonant tuning. From the simulation analysis, the slight increase of the parallel inductor value at the primary side can limit of the inverter current at uncoupled and high load resistor conditions. The proposed system also offers higher efficiency than the series-series detuned compensation and slightly lower than the double-sided LCC compensation network at different coupling factor.